Control of the oscillator strength of the exciton in a single InGaN-GaN quantum dot - Jarjour, A; Oliver, R; Tahraoui, A; Kappers, M; Humphreys, C; Taylor, R (American Physical Society, 2007)
We report direct evidence for the control of the oscillator strength of the exciton state in a single quantum dot by the application of a vertical electric field. This is achieved through the study of the radiative lifetime of a single InGaN-GaN quantum dot in a p-i-n diode structure. Our results are in good quantitative agreement with theoretical predictions from an atomistic tight-binding model. Furthermore, the increase of the overlap between the electron and hole wave functions due to the applied field is shown experimentally to increase the attractive Coulomb interaction leading to a change in the sign of the biexcitonic binding energy.